How to Treat Type B Aortic Dissections in the Presence of an Aberrant Right Subclavian Artery: A Systematic Review - Lombardi, Francesco; Mamopoulos, Apostolos; Benedik, Jaroslav; Katoh, Marcus; Kröger, Knut; Gäbel, Gabor (AORTA, 2023)
An aberrant right subclavian artery (ARSA) is the most common congenital variant of the aortic arch. Usually, this variation is largely asymptomatic, but sometimes it may be involved in aortic dissection (AD). Surgical management of this condition is challenging. The therapeutic options have been enriched in recent decades by establishing individualized endovascular or hybrid procedures. Whether these less invasive approaches bear advantages, and how they have changed the treatment of this rare pathology, is still unclear. Therefore, we conducted a systematic review. We performed a review of literature from the past 20 years (from January 2000 until February 2021) complying with the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. All reported patients treated for Type B AD in the presence of an ARSA were identified and classified into three groups according to the received therapy (open, hybrid, and total endovascular). Patient characteristics, as well as in-hospital mortality, and major and minor complications were determined and statistically analyzed. We identified 32 relevant publications comprising 85 patients. Open arch repair has been offered to younger patients, but significantly less often in symptomatic patients needing urgent repair. Therefore, the maximum aortic diameter was also significantly larger in the open repair group compared with that in the hybrid or total endovascular repair group. Regarding the endpoints, we did not find significant differences. The literature review revealed that open surgical therapies are preferred in patients presenting with chronic dissections and larger aortic diameters, most likely because they are unsuitable for endovascular aortic repair. Hybrid and total endovascular approaches are more often applied in emergency situations, where aortic diameters remain smaller. All therapies demonstrated good, early, and midterm outcomes. But, these therapies carry potential risks in the long term. Therefore, long-term follow-up data are urgently needed to validate that these therapies are sustainable.
Keywords: aberrant right subclavian artery; arteria lusoria; Type B aortic dissection